Medical Assistance System for Differentially Abled People using Arduino Lilypad - Prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
An assistance system for providing medical aid to differentially abled people has been presented in this paper. It is controlled by wireless gestures. The gesture is detected by a sensor (accelerometer) and it is responsible for controlling the robot that provides assistance and a wireless command will be given by a microcontroller which depends on the value of a sensor for moving it to the particular location. The whole process is divided into two parts: a circuit for transmission and another for receiving. The association of a part to a patient is one of the most important part of a medical assistance system and transmission circuit in this case is wearable. Thus it is easy to use. This project uses Arduino Lilypad for enabling a transmitting circuit to be wearable and it is the chief controlling microcontroller. This circuit is worn on that part of the body of a patient which is intended for making a gesture. The wireless transmission of data is done by RF module and Arduino IDE.na is used for programming.